Accrual Budgeting and Fiscal Policy - Robinson, Marc. (Washington, D.C. : International Monetary Fund, 2009)
Can an accrual budgeting system-a system in which budgetary spending authorizations to line ministries are formulated in accrual terms-serve the needs of good fiscal policy? If so, how must such a system be designed? What are the practical challenges which may arise in implementing sound fiscal policy under a budgeting system which is significantly more complex than traditional cash budgeting? These are the primary questions addressed in this paper. Because any budgeting system must support the control of key fiscal policy aggregates, the paper also considers the case for reformulating fiscal policy in terms of accrual rather than cash aggregates. The primary focus is on the potential fiscal policy role of net lending and net financial debt. However, the paper also considers whether net worth is an aggregate with major fiscal policy relevance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet